Growth and Yield of Seven Tree Species under High Density Planting and Irrigation - Nadagouda, V. B.; Patil, C. V.; Desai, B. K.; Manjappa, K. (Indian Forester, 1997)
The performance of seven tree species, Acacia auriculiformis, Azadirachta indica, Dendrocalamus strictus, Dalbergia sissoo, Eucalyptus, Leucaena leucocephala and Tectona grandis under high density planting (60 Ã— 60 cm) was evaluated on irrigated red sandy clay loam soils of Regional Research Station, Raichur, Karnataka during the period from 1983 to 1988. At the end of fifth year, Eucalyptus produced significantly the highest wood yield (105 t ha -1) as compared to other tree species. The lowest wood yield (28.1 t ha-1) was recorded in Tectona grandis. The net returns realised from wood yield was also more from Eucalyptus (Rs. 54,450 ha-1) followed by Azadirachta indica (Rs. 46,602 ha -1) and Leucaena leucocephala (Rs. 43,857 ha -1), while the lowest net returns (Rs. 18,522 ha -1) was realised from Dendrocalamus strictus.